The Effect of Tube Diameter on an Atmospheric‐Pressure Micro‐Plasma Jet. Issue 12 (21st September 2015) - Cheng, He; Lu, Xinpei; Liu, Dawei
Abstract : The micro‐plasma jet is a unique way of transporting active species of plasma to small targets for applications such as a single cancer cell treatment, and endoscopic surgeries. In this letter, the authors present numerical studies on a single cylindrical electrode micro‐plasma jet. The effect of tube diameter on sustaining voltage, electron density, and the density of reactive species are investigated. The diameter of the dielectric tube was varied in the range between 0.1 and 1mm. A pulsed direct current voltage with rising phase of 50 ns was used to ignite the plasma jet. The sustaining voltage monotonically increased with the decreasing diameter of the tube. More electrons wall losses happened due to the faster drift movement to the inner wall of smaller tube diameter, therefore, the decreasing pre‐avalanche electron density need increasing ignition voltage to facilitate the avalanche‐streamer transition as the tube diameter decreased. The increasing ignition voltage increased the chemical reactivity of plasma jet. The peak density of O2 * and O increased more than 20 times as the tube diameter decreased from 1 to 0.1 mm. Abstract : The micro‐plasma jet is a unique way to treat small targets for biomedical applications . A numerical study on a single cylindrical electrode micro‐plasma jet was carried out. Because of the faster drift movement of electrons to the inner wall of dielectric tube, more electrons wall losses happened before the avalanche as tube diameter decreased. The decreasing pre‐avalanche electron density need increasing sustaining voltage to cause the avalanche‐streamer transition. The increasing ratio of sustaining voltage as tube diameter decreased is consistent with the experimental measurement. The increasing sustaining voltage increased the chemical reactivity of micro‐plasma jet.